TEACHING STRATEGY IN ENRICHING THE EFL STUDENTS’ VOCABULARY THROUGH LITERATURE - Baharuddin, Andi Farid; Nur, Sahril; Isma, Adi (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2022)
Vocabulary acquisition is one of the important elements that can support the students’ language proficiency. It helps students to follow and enjoy the teaching content delivered by their teachers. The educator of the EFL context, particularly at lower secondary school, attempts to design the teaching material which is oriented to enrich the students’ vocabulary acquisition. The research discovers that various ways can be used to build students’ vocabulary. One of them is literature. Therefore, this research aims to investigate can English literary works be integrated with the teaching strategies to develop the EFL students’ vocabulary. To observe it, the researchers use library research to find and analyze some sources (e.g. articles, proceedings, books) as the collected data, which discuss enriching English vocabulary through literature. The result shows that two things must be considered if teachers would like to incorporate literary works in their content. 1) Types of literary works used by teachers to enhance their learners’ vocabulary, 2) Teacher’s teaching strategy to make the EFL learners memorize the unrecognize words.